Lipidomics in Health & Disease Methods & Application (Translational Bioinformatics,, 2018)
This volume covers the emerging area of science, Clinical Lipidomics, which is the application of lipidology to the understanding of physiological and pathophysiological changes of lipidomes, with a special focus on lipidomic profiles in human diseases. Lipidomics is widely used to map lipid molecular species in a biological system. Clinical lipidomic analysis has demonstrated the comprehensive characterization of molecular lipids in various severities, durations, and therapies as a critical tool in identification and validation of disease-specific biomarkers. This volume on Clinical Lipidomics will add to the literature and help advance the knowledge of the pathogenesis, diagnosis, prevention and treatment of diseases. .